Radical resection of an initially unresectable intrahepatic cholangiocarcinoma after chemotherapy with using gemcitabine, cisplatin, and S-1: report of a case - Masashi Tsunematsu; Koichiro Haruki; Taro Sakamoto; Tadashi Uwagawa; Hiroaki Shiba; Katsuhiko Yanaga (Surgical Case Reports)
Abstract Background Metastatic biliary tract cancer (BTC) has poor prognosis. Recently, patients with metastatic BTC who respond well to systemic chemotherapy can be treated by radical resection or “conversion surgery.” Case presentation A 67-year-old male patient was diagnosed with intrahepatic cholangiocarcinoma with para-aortic metastases [cT2N1M1, stage IVB]. He was enrolled in our phase II study for unresectable BTC consisting of cisplatin (25 mg/m2 i.v. for 30 min) followed by gemcitabine (1000 mg/m2 i.v. for 30 min) on days 1 and 8 and oral S-1 on alternate days. After 8 courses of this regimen, marked regression of para-aortic lymph metastases was achieved, and we performed extended left hepatic lobectomy with the caudate lobe, concomitant portal vein resection, and lymph node dissection including the para-aortic region. The patient made a satisfactory recovery and was discharged on postoperative day 25. Histopathological examination revealed more than 50% of the tumor area replaced with fibrosis, and curative resection was achieved (ypT2N1M1, stage IVB, Evans criteria IIb). The patient received adjuvant chemotherapy using S-1 for 12 months and remains well with no evidence of tumor recurrence as of 48 months after surgery. Conclusions We herein report a successfully treated case of advanced BTC with para-aortic lymph node metastases by conversion surgery after combination chemotherapy using gemcitabine, cisplatin, and S-1.